Segmentasi Wajib Pajak UMKM Menggunakan Analisis Cluster dan Pengaruhnya terhadap Kepatuhan Pajak - Febiyanti .; Najwa Dara; Metha Amelia; Desvieta Fathinnisa; Dimas Apta; Rizky Hidayatullah; Ihsan Fahmiruddin (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study reveals a key phenomenon: MSMEs contribute significantly to the West Java economy, yet they face tax compliance challenges due to a lack of understanding of tax issues. Data from 45 respondents showed that 66.67% did not understand tax rules and procedures, 80% had never attended tax outreach, 68.89% did not have a Taxpayer Identification Number (NPWP), and 88.89% did not keep financial records, thus tax was considered a complex burden that hampered cash flow. Therefore, this study aims to examine the segmentation of MSME taxpayers and its impact on tax compliance in West Java through a descriptive qualitative approach with cluster analysis. Data were collected through in-depth interviews and open-ended questionnaires with 45 MSMEs. The results classified taxpayers into three clusters based on business size, income, tax knowledge, and compliance motivation. Cluster analysis revealed inequalities, with micro MSMEs with unstable incomes tending to be less compliant than the more informed middle class. This reflects MSMEs' limited access to the national tax system, despite government simplification of regulations. Therefore, cluster analysis is effective for policy interventions such as tax education and simplified procedures.